ANALISIS INDIKASI KECURANGAN BERBASIS FRAUD DIAMOND PADA SIKLUS PERSEDIAAN DAN PERGUDANGAN PT. PERCETAKAN SUMBER JAYA - Fatimatul Zahro; Senny Harindahyani (Perpustakaan Universitas Surabaya, 2018)
Abstract - This study aims to obtain an overview of the internal controls in the warehouse cycle and inventory cycle and identify indications of fraud that occur using diamond fraud. Furthermore provide recommendations of PT. Percetakan Sumber Jaya related internal controls to minimize the cheating gap. The result of the research indicates that there is an indication of fraud on inventory and warehouse cycle when analyzed using fraud diamond due to weak internal control applied to the cycle. Weak controls create a gap in receipt of raw materials, raw material expenditure and internal auditors owned less competent. So companies need to implement appropriate and effective controls for medium-sized companies is COSO. However, as a complement to minimize fraud and prevent fraud gaps, accounting controls and administrative controls can be used. In addition, the company must also have a competent internal auditor and perform its duties based on internal auditor standards.